2012
DOI: 10.1017/s104161021200213x
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural differences in dementia: the Sociocultural Health Belief Model

Abstract: The SHBM provides an empirically based conceptual framework for examining cross-cultural differences in dementia care-seeking among diverse groups. We provide recommendations for future research, such as the need for research with more diverse ethnic subgroups and the examination of group-specific cultural values. We conclude with a discussion of the clinical and service implications of our review, including potential interventions aimed at facilitating timely dementia diagnoses among ME older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(113 citation statements)
references
References 54 publications
4
106
3
Order By: Relevance
“…This is surprising, especially since studies in other minority groups showed that low levels of knowledge, different beliefs, and attitudes as well as increased stigmatic beliefs and feelings of shame delay their access to services and their help-seeking patterns. 38,39 The few studies conducted in Israel corroborate these patterns among the Israeli Arab minority. Indeed, compared to the Jewish population, low levels of objective and perceived knowledge were found, stressing the importance of developing educational programs, specially geared to increase knowledge and awareness in this population.…”
Section: Summary Conclusion and Research Recommendationsmentioning
confidence: 91%
“…This is surprising, especially since studies in other minority groups showed that low levels of knowledge, different beliefs, and attitudes as well as increased stigmatic beliefs and feelings of shame delay their access to services and their help-seeking patterns. 38,39 The few studies conducted in Israel corroborate these patterns among the Israeli Arab minority. Indeed, compared to the Jewish population, low levels of objective and perceived knowledge were found, stressing the importance of developing educational programs, specially geared to increase knowledge and awareness in this population.…”
Section: Summary Conclusion and Research Recommendationsmentioning
confidence: 91%
“…Individuals who perceive memory loss as a natural part of aging may be more likely to overlook behavioral and cognitive symptoms of dementia and thus less likely to seek medical care. In addition to delaying medical care, minority groups tend to experience other barriers, including less knowledge about dementia and less access to health services (Sayegh & Knight, 2013).…”
Section: Cultural Differencesmentioning
confidence: 99%
“…It is possible that education-level differences, language barriers, and ethnocultural differences in how BPSD are interpreted and communicated may have influenced ethnic-group differences on responses to the NPI-Q items. Additionally, the shame and stigma associated with dementia and its BPSD may be particularly salient among Hispanics (Sayegh & Knight, 2013), which could have systematically influenced response patterns across ethnic groups. Similarly, informant-reporting styles on patients' BPSD may have differed across groups given that Hispanic caregivers may be more sensitive to BPSD than NHW caregivers (Valle, 1994).…”
Section: Neuropsychiatric Inventory Questionnairementioning
confidence: 99%
“…A number of possible reasons exist that may lead to ethnic-group differences in response patterns on these scales, including linguistic barriers, ethnocultural influences on the perception and communication of dementia symptoms, and shame and stigma associated with dementia (Sayegh & Knight, 2013). If the FAQ and NPI-Q do not demonstrate ethnic-group measurement invariance, then explanations of across-group differences are called into question, as is clinical diagnostic validity.…”
mentioning
confidence: 99%